Oesophageal pressure and motility with special reference to the mechanism of deglutition - Botha, Gideon Stephanus Muller (Department of Medicine, 2020)
This thesis is primarily concerned with oesophageal motility, but certain aspects of the mechanism of deglutition were also studied in detail, either deliberately or by chance. · All dissections, experiments and microscopical and other examinations were conducted by the author and some specimens personally blocked, Out and stained. The liberal use of illustrations clarifies many points which otherwise would not have been so convincingly described; they also ,emphasise strongly the wide variation of normal, which unfortunately we only too often lose sight of in medicine. The literature on this wide subject is so vast that it cannot be completely covered or referred to in a thesis of this nature. The references at the end of this thesis are mainly recent and should, give the·reader·some indication of the divergence of opinion and current concepts on this complex subject.